2010
DOI: 10.4097/kjae.2010.59.1.22
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous low dose ketamine for reducing postoperative sore throat

Abstract: BackgroundThis study was performed to evaluate the effectiveness of intravenous low dose ketamine for reducing the incidence and severity of postoperative sore throat (POST).MethodsThis was a prospective, randomized, double-blind clinical trial. The study population consisted of 70 patients between 20 and 70 years old who were classified as American Society of Anesthesiologists I-II and were scheduled for elective laparoscopic cholecystectomy. The patients were divided randomly into two groups. Patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…[135456781314] There was no incidence of POST at 12 and 24 h for ketamine and 24 h for magnesium sulfate 500 mg. This could be because of the persistent local action of ketamine and magnesium even at that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[135456781314] There was no incidence of POST at 12 and 24 h for ketamine and 24 h for magnesium sulfate 500 mg. This could be because of the persistent local action of ketamine and magnesium even at that time.…”
Section: Discussionmentioning
confidence: 99%
“…[4] who had also reported no significant difference in the incidence of cough postoperatively following ketamine gargle.…”
Section: Discussionmentioning
confidence: 99%
“…Sore throat and hoarseness occur after total intravenous anesthesia with ketamine ( 18 ) that shows systemic effect is not of much importance in alleviating sore throat. In fact, intravenous injection of low dose ketamine is not effective in reducing postoperative sore throat ( 19 ). In addition, previous reports insisted on lesser analgesic systemic levels of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Because we did not measure ketamine levels in the plasma, we could not rule out the influence of a systemic effect of ketamine. However, Park et al [19] reported that intravenous low-dose ketamine injection was not effective for reducing POST, and Chan et al [20] reported that systemic absorption during ketamine gargling did not play a major role in the reduction of POST. In the present study, the topical effect (rather than the systemic effect) may have contributed to the outcome.…”
Section: Discussionmentioning
confidence: 99%